A158 ENTEROPATHOGEN CYSTEINE PROTEASES ALTER INTESTINAL MUCUS PRODUCTION VIA PROTEASE-ACTIVATED RECEPTOR-2: EFFECTS OF GIARDIA DUODENALIS. (15th March 2019) - Fekete, E; Amat, C B; Allain, T; Hollenberg, M; Chadee, K; Buret, A
Abstract: Background: Disruption of the intestinal mucus barrier can impair host innate immunity and has been implicated in many GI disorders. We recently showed that the intestinal protozoan parasite Giardia duodenalis alters host intestinal mucus layers via obscure mechanisms. Giardia offers a powerful model system to study regulatory mechanisms governing intestinal mucus production and secretion in health and disease. As Giardia is known to secrete proteases, we hypothesized that goblet cell mucus production may be regulated via protease-activated receptor-2 (PAR2). Aims: To characterize mechanisms responsible for Giardia -mediated alterations of mucus production, including the roles of PAR2 and Giardia proteases. Methods: LS174T, a human mucus-producing colon cell line, was infected with Giardia trophozoites (isolates NF, WB, S2, and GSM ). Before infection, trophozoites were treated with E64, a broad-spectrum cysteine protease inhibitor, and LS174T were treated with a pepducin PAR2 antagonist, or BAPTA, a calcium chelator. Quantitative PCR (qPCR) was performed for the MUC2 mucin gene. Chinese hamster ovary cells transfected with nano-luciferase tagged PAR2 were incubated with Giardia NF or GSM trophozoites, which cleaved receptors to release enzymes. Luminescence was measured as an indicator of PAR cleavage and therefore potential of Giardia to activate PAR2. Wild-type (WT) and PAR2 deficient (PAR2-/-) mice were infected with Giardia trophozoites. Colonic mucus was stained using fluorescein-coupled wheat-germ agglutinin and qPCR was performed for Muc2 and Muc5ac. Results: Giardia NF, S2, and WB, but not GSM, increased MUC2 gene expression in LS714T. Increases were attenuated by inhibition of Giardia cysteine protease activity and by antagonism of PAR2 or inhibition of calcium release in LS174T. Giardia trophozoites cleaved PAR2 at the N-terminus suggesting they may activate PAR2. Cleavage efficiency was isolate dependent and reflected differences in protease activity between isolates. Cysteine protease inhibition significantly reduced cleavage. Giardia infected WT mice show increased colonic expression of Muc2 and Muc5ac, and increased Muc5ac but decreased Muc2 expression in the jejunum. These changes were not demonstrated in PAR2-/- mice. WT infected and PAR2-/- noninfected mice showed thinning of the colonic mucus layer compared to WT controls. There was some recovery in thickness in PAR2-/- infected mice. Conclusions: Results show that PAR2 plays a significant role in the regulation of mucin gene expression in mice and a human colon cell line. Results suggest that Giardia cysteine proteases cleave and activate PAR2 on intestinal goblet cells, leading to calcium release and ultimately altered mucin gene expression. Findings identify a novel regulatory pathway for goblet cell mucus production in the gut. Funding Agencies: CCC